The Efficacy of Metacognition in the Academic Performance of International Students in a Diverse and Inclusive University Through the Lens of Bandura Social Cognitive Theory - Okojie, Stephen O. (Advances in Social Sciences Research Journal, 2025)
This qualitative study aimed to explore the role of metacognition in the academic performance of international students at a diverse and inclusive university through the lens of Bandura’s social cognitive theory. The study involved in-depth interviews with 20 purposefully sampled international students from various cultural backgrounds enrolled at the university. The interviews concentrated on understanding the students’ perceptions and experiences regarding their metacognitive processes and their impact on academic performance. Thematic analysis was performed to identify recurring themes and patterns in the data. The findings revealed that metacognition plays a crucial role in the educational performance of international students. Participants indicated that being aware of their learning strategies, setting goals, monitoring their progress, and adjusting their approaches based on feedback significantly influenced their academic performance. This study offers valuable insights into the significance of metacognition in the academic performance of international students, as backed by Bandura’s social cognitive theory, highlighting the necessity for educational interventions that enhance students’ metacognitive skills in a diverse and inclusive university environment.